Exploring Biomarkers in Gestational Diabetes Mellitus: A Comprehensive Review - Dhivya Senthil Kumar; Sathya Selvarajan; KS Rajeswari (Journal of Clinical and Diagnostic Research, 2024)
Gestational Diabetes Mellitus (GDM) is a common complication during pregnancy, typically diagnosed in the second or third trimester. Factors such as advanced maternal age, obesity and a sedentary lifestyle contribute to its prevalence. The pathophysiology involves insulin resistance, β-cell dysfunction, gluconeogenesis, adipose tissue dysfunction, gut microbiota dysbiosis and oxidative stress. GDM is associated with maternal and neonatal complications, both short-term and long-term. Managing GDM requires interventions such as medication, dietary adjustments and regular physical activity. However, early detection in low-risk populations remains challenging. The Oral Glucose Tolerance Test (OGTT) is the gold standard for diagnosis but is limited by its inconvenience and reliance on multiple blood samples. The present review focuses on novel biomarkers for early and accurate GDM diagnosis. It discusses emerging biomarkers such as vitamin D, vitamin B9, vitamin B12, preptin, angiopoietin-like protein 8, adiponectin, chemerin, omentin-1, leptin, Interleukin-6 (IL-6), homocysteine, C-peptide, irisin, adropin, nesfatin-1, Afamin, fetuin A, amylin, galectin, osteocalcin, resistin, visfatin and Fatty Acid-binding Protein 4 (FABP4). The review explores the pathophysiology of these biomarkers in GDM and presents preliminary study findings.